Adaptabilidad de pastos, en la comuna jurídica Cubinche, Tabacundo – Ecuador 2013. - Sánchez Valladares, José Luis (2015)
In the commune Cubinche Legal, parish Hope, Pedro Moncayo Canton, province of Pichincha, assessed the adaptability by species and mixing of the pasture Medicago sativa (Alfalfa variety CUF101), Trifolium pratense (Red Clover variety Freedom), Festuca arundinacea (Festuca variety Barolex) and Dactylis glomerata (Blue Grass) for 270 days. Design was a randomized complete block with 8 treatments and 4 repetitions. The best performance and economic behavior presented the mix Alfalfa + Tall Fescue with an average of 28381.10 kilograms of dry matter per hectare per year and $2.51 profit cost.